2015
DOI: 10.1038/ncomms9148
|View full text |Cite
|
Sign up to set email alerts
|

Development of high-yield influenza A virus vaccine viruses

Abstract: Vaccination is one of the most cost-effective ways to prevent infection. Influenza vaccines propagated in cultured cells are approved for use in humans, but their yields are often suboptimal. Here, we screened A/Puerto Rico/8/34 (PR8) virus mutant libraries to develop vaccine backbones (defined here as the six viral RNA segments not encoding haemagglutinin and neuraminidase) that support high yield in cell culture. We also tested mutations in the coding and regulatory regions of the virus, and chimeric haemagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 54 publications
0
81
0
3
Order By: Relevance
“…To characterize the receptor-binding properties of the viruses tested here, we used a glycan array in which 129 diverse sialic acid-containing glycans were printed on a microarray (Table S8). Recombinant viruses possessing the HA and NA genes of GD/3, Anhui/1, or A/Kawasaki/173/2001 (H1N1; K173; chosen because of its known human-type receptor-binding specificity; (Imai et al, 2012) and the remaining genes from A/Puerto Rico/8/34 (H1N1; PR8) (Ping et al, 2015) were generated by reverse genetics, and subjected to glycan array analysis. K173 virus bound preferentially to α2,6-linked glycans (Figure 6A), as expected.…”
Section: Resultsmentioning
confidence: 99%
“…To characterize the receptor-binding properties of the viruses tested here, we used a glycan array in which 129 diverse sialic acid-containing glycans were printed on a microarray (Table S8). Recombinant viruses possessing the HA and NA genes of GD/3, Anhui/1, or A/Kawasaki/173/2001 (H1N1; K173; chosen because of its known human-type receptor-binding specificity; (Imai et al, 2012) and the remaining genes from A/Puerto Rico/8/34 (H1N1; PR8) (Ping et al, 2015) were generated by reverse genetics, and subjected to glycan array analysis. K173 virus bound preferentially to α2,6-linked glycans (Figure 6A), as expected.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of such efforts include the following: Improvement of the global strain‐selection process, coordinated by WHO, to incorporate newer methods for predicting virus evolution and drift and identification of virus vaccine candidates 23, 24 Increasing the availability of more high‐yield candidate vaccine viruses, including candidate vaccines that are optimized for specific production systems (e.g., cell‐based or egg production) 25, 26 Coordinating reagent production among regulatory agencies to address resource issues and developing backup strategies for reagent production to ensure availability in the case of unexpected problemsAccelerating the process of potency reagent calibration and developing improved methods for vaccine testing, such as new methods for testing potency and sterilityDeveloping new types of influenza vaccines with greater cross‐protection and longer duration of protectionIdentifying issues related to development and evaluation of novel influenza vaccines so that appropriate regulatory pathways can be employed to facilitate licensure …”
Section: Resultsmentioning
confidence: 99%
“…Increasing the availability of more high‐yield candidate vaccine viruses, including candidate vaccines that are optimized for specific production systems (e.g., cell‐based or egg production) 25, 26 …”
Section: Resultsmentioning
confidence: 99%
“…The use of mammalian cells, e.g., Madin-Darby canine kidney (MDCK) cells and African monkey kidney cells (Vero), for the production of influenza viruses has been evaluated. Recently, Ping et al reported that a novel high-yield PR8 vaccine backbone strain isolated from random mutant virus libraries led to improvement in influenza vaccine titers in MDCK and Vero cells (47). Our findings may be additionally applied to mammalian cell-based systems for improving the efficiency of vaccine production.…”
Section: Discussionmentioning
confidence: 96%